Characterization of a novel RNA-binding region of eIF4GI critical for ribosomal scanning - Prévôt, Déborah (Oxford University Press, 2003)
The eukaryotic translation initiation factor eIF4GI binds several proteins and acts as a scaffold to promote preinitiation complex formation on the mRNA molecule (48S). Following mRNA attachment this complex scans along the messenger in a 5′ to 3′ direction until it locates and recognizes the initiation start codon. By using a combination of retroviral and picornaviral proteases (HIV-2 and L respectively) in the reticulocyte lysate system, we have characterized a 40 amino acid (aa) region of eIF4GI (aa 642–681) that exhibits general RNA-binding properties. Removal of this domain by proteolytic processing followed by translational assays showed virtually no inhibition of internal ribosome entry on the encephalomyocarditis virus, but resulted in drastic impairment of ribosome scanning as demonstrated by studying poliovirus and foot-and-mouth disease virus translation. Based on these findings, we propose that this 40 aa motif of eIF4GI is critical for ribosome scanning.